2023
DOI: 10.3389/fenvs.2023.1167581
|View full text |Cite
|
Sign up to set email alerts
|

The effects of environmental regulation and environmental protection investment on green technology innovation of enterprises in heavily polluting industries—based on threshold and mediation effect models

Abstract: Introduction: Studying the influence and mechanism between environmental regulation, environmental protection investment, and enterprise green technology innovation is crucial to realize ecological civilization construction and sustainable economic growth.Methods: Based on the green patent data and the corresponding enterprise data of A-share heavily polluting industry enterprises from 2010 to 2020, a comprehensive index of environmental regulation is constructed, and the system GMM estimation method, threshol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…For example, Song et al [15] found a U-shaped relationship between ER and GI, indicating that as ER increases, its role will gradually change from suppressing to stimulating GI. Yang and Zhao [16], as well as Khattak [17], studied the impact of ER on GI and arrived at the same conclusion.…”
Section: Introductionmentioning
confidence: 60%
“…For example, Song et al [15] found a U-shaped relationship between ER and GI, indicating that as ER increases, its role will gradually change from suppressing to stimulating GI. Yang and Zhao [16], as well as Khattak [17], studied the impact of ER on GI and arrived at the same conclusion.…”
Section: Introductionmentioning
confidence: 60%